Systematic review: Digital recovery support services used to support substance use disorder recovery. Issue 1 (30th April 2019) - Ashford, Robert D.; Bergman, Brandon G.; Kelly, John F.; Curtis, Brenda
Abstract: Substance use, misuse, and disorders (SUDs) are estimated to cost the United States over 500 billion annually. While there are effective SUD behavioral interventions and treatments, there is mounting evidence that technology‐based, digital recovery support services (D‐RSS) have the potential to prevent SUD, complement formal treatment, and improve individual recovery‐related outcomes. This preregistered systematic review focuses on D‐RSS that provide SUD recovery support through websites, smartphone applications, recovery social network sites, or any combination thereof. Data sources included studies found in searching CINAHL Plus (EBSCO), EMBASE, MEDLINE (EBSCO), Index Medicus/MEDLINE (NLM), Psychology & Behavioral Sciences Collection (EBSCO), PsycINFO (ProQuest), ProQuest Psychology Journals (ProQuest), and retrieved references. Observational, mixed‐methods, qualitative, or experimental studies, published in English, between January 1985 and January 2019, that characterized users and recovery‐related outcomes of any D‐RSS were included. The initial search yielded 5, 278 abstracts. After removing duplicates, as well as reviewing titles and abstracts and removing studies not indicating an examination of recovery (i.e., treatment or prevention focused) and digital supports, 78 abstracts remained. Final included studies ( n = 22) characterized international users of multiple D‐RSS types, including websites, digital recovery forums, recovery social networking sites, smartphone applications, and short messaging service texting programs. Experimental evidence was lacking as most studies were observational or qualitative in nature ( n = 18). The review suggests that the evidence base for most D‐RSS is still lacking in terms of demonstrating benefit for recovery‐related outcomes. Descriptively, D‐RSS have high usage rates among engaged participants, across a range of SUD and recovery typologies and phenotypes, with 11% of U.S. adults who have resolved a SUD reporting lifetime engaging with at least one D‐RSS. D‐RSS deployment can help ameliorate barriers related to accessibility and availability of more traditional recovery supports, and may well be a valuable tool in addressing SUD and supporting recovery as uptake increases across the United States.